Gully erosion in winter crops: a case study from Bragança area, NE Portugal - Figueiredo, Tomás de (2011)
This text is an adapted and extended version of a poster presentation, quoted below, and was also the subject of a lecture prepared for SPinSMEDE 2008 edition. Discussion of this case study, although a very important part of the lecture, is not included in this text. Quotation is: Figueiredo, T. de, Poesen, J., Vandekerckhove, L., Oostwoud-Wijdenes, D., Araújo, J. 2000. Contribution of ephemeral gullies to erosion on cultivated areas: field measurements in four small catchments in Bragança, NE Portugal. Poster presented to International Symposium on Gully Erosion under Global Change, Catholic University of Leuven, Belgium, April 16-19, 2000 (book of abstracts).